Dentistry students' views about mental illness and impact of a targeted seminar on knowledge and attitudes: a mixed-method study. Issue 3 (2nd September 2014) - Patterson, Susan; Ford, Pauline
Abstract : Purpose: – The purpose of this paper is to inform education of non-mental health professionals who provide care to people with severe mental illness; to describe dentistry students' knowledge and views about mental illness, including willingness to engage in various social situations with a person hospitalised for mental illness; and to assess and understand the impact of a targeted lecture on views and attitudes. Design/methodology/approach: – The paper employed mixed methods to examine dental students' knowledge and views about mental disorder before and after a seminar covering mental disorder, disadvantage and oral health. Findings from a bespoke questionnaire administered to third-year dental students were triangulated with qualitative data gathered in interviews with a subsample. Findings: – Students understood mental disorder broadly, employing diverse causal models. Although knowledge was typically grounded in media stereotypes, attitudes were benevolent and most students reported willingness to provide dental care to affected individuals. The seminar, especially the consumer delivered section, was valued and associated with increased appreciation of the impact of mental disorder on oral health and need for assertive action to promote access to care. However, students reported being reluctant to disclose their own mental health problems for fear of being considered a professional or personal failure. A minority knew how to seek support if a friend talked of suicide. Research limitations/implications: – This study highlights the need for further investigation of the knowledge and attitudes of dentistry students pertinent to provision of care to people with mental illness and to examine the links between attitudes and practice. The paper also provides a useful foundation for development of brief educational interventions, particularly the value in integrating the service user perspective, and their evaluation. Research should also examine the impact of mental health education on practice. Practical implications: – A single inexpensive educational session, such as the one the paper developed may support reconsideration of often unconscious views of mental illness which might affect practice. Social implications: – If people with mental illness are to receive equitable access to health care, non-mental health professionals should be supported to develop knowledge and attitudes which are conducive to inclusive treatment. An education session such as this could be helpful. Originality/value: – There is scant literature examining attitudes of dentistry students and no reports of mental health-specific education with this population.